A Superconvergence Analysis for Finite Element Solution by the Interpolant Postprocessing on Irregular Meshes for Smooth Problem (Journal of Computational Mathematics, 2001)
The post-processing procedure is given by an interpolant postprocessing of the finite element solution by appropriately-defined finite dimensional subspaces. The corresponding superconvergence is established on general quasi-regular finite element partitions.